THE PLACE OF MAVLANO JALALIDDIN RUMI'S SPIRITUAL HERITAGE TODAY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides information about the work of Jalaluddin Rumi and his rare works. The place of Rumi's spiritual heritage in literature and today is discussed.